Microorganisms and Moonmilk in the non-ornated caves from the Vézère Valley (Dordogne, France) - Bhattacharya, Sriradha (2022)
Microorganisms inhabit all possible environments including hypogean environments. Cave are the best examples of a glimpse into the subsurface world and into human past through its art work. Microbes are often harmful for cultural assets (eg, paleolithic paintings), because they are related to constructive (mineral precipitation) and destructive (substrate dissolution) processes affecting different substrates (hostrock, speleothems, paintings, etc.). Moonmilk, a secondary speleothem is a problem that plagues this art. The environment is very distinct as they differ vastly from the exterior owing to it being divided by the soil and the epikarst. Caves are considered as extreme environments due to very little or complete absence of sunlight and limited interaction with the outside ecosystem. This determines the growth of microorganisms that can easily adapt to these extreme conditions playing an important role in the development of biotransformations inside the caves, namely biomineralization and probably in the formation of moonmilk and leading to potential degradation of cave art. Moonmilk is identified by its distinctive crystalline fibre, referred to as Needle Fibre Calcite (NFC).